Accuracy and precision of photoacoustic spectroscopy not guaranteed - Rosenstock, Todd S.; Díaz Pinés, Eugenio; Zuazo, Pablo; Jordan, G.; Predotova, M.; Mutuo, P.; Abwanda, Sheila O.; Thiong'o, M.; Buerkert, Andreas; Rufino, Mariana C.; Kiese, Ralf; Neufeldt, Henry; et al. (Wiley, 2013)
Because of their accuracy and precision for measuring gas concentrations, gas chromatographs (GC) are standard analytical instruments used in investigations of nitrous oxide (N2 O) and carbon dioxide (CO2 ) exchange between the soil and the atmosphere. Iqbal et al. (2012) indicate that photoacoustic spectroscopy (PAS) performs similar to GCs for this purpose. We welcome this addition to the literature, given the increasing number of studies using PAS (e.g., Predotova et al. 2009; Leytem et al. 2011) and the few comparative analyses available (Ambus & Robertson 1998; Yamulki & Jarvis 1999). However, poor performance of PAS in some assessments (Akdeniz et al., 2009) and data from our own tests (reported below) raise questions about whether Iqbal et al.'s (2012) results are generally applicable to PAS instruments or unique to the experimental conditions and calibration of their instruments.